ANALISIS PENGHAMBAT AKSES PENDANAAN USAHA KECIL MIKRO DAN MENENGAH DI KABUPATEN KONAWE SELATAN - Akbar Wahbi; Jamal; Bakti; La Ode Mahmud; Waode Harliyanti Unga (Halu Oleo University, 2024)
This research aims to determine the factors inhibiting access to MSME funding that occur in the South Konawe Regency. The method in this research uses qualitative research methods with a descriptive approach. The data collection method was carried out by conducting interviews with MSME actors and the Cooperative and MSME Service in South Konawe Regency. From the results of the research carried out, it was found that several factors cause obstacles to access to funding, namely, there are still many MSME actors who do not legalize their businesses using their Nomor Induk Berusaha (NIB) and the lack of assistance provided by the government through the Cooperatives and MSMEs Service to business actors in South Konawe Regency.